Varicocele - literature review - Sowiński, Wojciech; Walentyn, Wiktoria; Wachowska, Maria; Molenda, Marek; Woszczyńska, Oliwia; Rycąbel, Paweł; Romaniuk, Mateusz; Paniak, Mateusz; Szymura, Marta; Wojciechowska, Agnieszka; Krawczyk, Michał; Zdybel, Michał (Quality in Sport, 2025)
Introduction and objective Varicocele is the most common reversible cause of male infertility. This article describes the entire disease entity, in particular the pathophysiology and potential methods of treating this condition. Review methods A literature review was conducted using the PubMed database to gather knowledge about varicocele. The main search terms were ,,varicocele” , ,,varicocele pathophysiology”, and ,,varicocele treatment”. Description of the state of knowledge Varicocele is usually asymptomatic, and in other cases may cause nonspecific symptoms, such as discomfort or pain in the scrotum. Diagnosis is based on physical examination, and in doubtful cases, ultrasound can be used. There are several theories about the development of varicocele. These include the anatomical, nutcracker, embryological, or valve-related theories. Impaired blood flow from the testicles leads to oxidative stress and hyperthermia, which affects the deterioration of sperm quality. The most common indication for treating varicocele is difficulty getting pregnant. In such cases, non-pharmacological treatment is used. Conclusions The surgical techniques used differ in the frequency of complications, their type, and the percentage of improvement in semen parameters. Despite numerous successes in the treatment of varicocele, there remains a large group of patients who still have problems having children.